Unexpected questions in deception detection interviews: Does question order matter?. (5th April 2019) - Warmelink, Lara; Subramanian, Anna; Tkacheva, Daria; McLatchie, Neil
Abstract : Purpose: Unexpected questions have been shown to increase cues to deception, without reducing the information given by truth tellers. Two studies investigated whether the detail given by an interviewee is affected by whether the expected or unexpected questions are asked first. Methods: In Study 1, participants ( N = 85) were interviewed about their own intentions, and in Study 2, participants ( N = 84) were given an intention by the experimenter. They were then interviewed. Results: Results showed that in both studies, differences between the expected‐first and the unexpected‐first order were minimal and lie detection accuracy was not improved by asking the unexpected questions first. Conclusions: These results offer important information for forensic interviewers, showing that there is no need to ask unexpected questions at a certain point in the interview. Link to associated OSF page:https://osf.io/93g7h/?view_only=586daff060d846efb760c8155478ce9e .